(untitled) (Bodhi Path, 2025)
Buddhism is a religion of peace, humanism, and the spirit of scientific inquiry. If the human ideas of Lord Buddha are implemented for the benefit of society, then all forms of suffering in human society can be eradicated with ease. Buddhism is a collection of principles that help us understand the true nature of the self and develop our inherent human potential. In Buddhist philosophy, discussions are held on topics such as mutual relationships, practices, and causes and effects. These involve a detailed system of logic and reasoning that aids in comprehending the vast ideas of the philosophy. Buddhist ethics are based on the capability to differentiate between what is beneficial and what is harmful, both for oneself and for others. Buddhism fundamentally rejects the existence of an eternal God or soul. Instead, Buddha provided four noble truths regarding social suffering and showed the Middle Path as the way forward. Through the Middle Path, Buddha taught that humans should avoid all extremes of indulgence and asceticism. They should follow a balanced path that helps alleviate suffering. The essence of equanimity lies in maintaining a balanced state of mind and life, where neither excessive desires nor excessive restraint takes over. A balanced individual is one who controls their senses, practices meditation, and avoids harm to themselves or others. The Buddhist concept of moderation includes a balanced speech, action, and livelihood, referred to as the "Noble Eightfold Path." Various Buddhist texts explore this philosophy in depth, including the five moral precepts known as the Panchshila. Before joining the monastic order, individuals take vows based on the Panchshila: non-violence, truthfulness, refraining from theft, abstaining from harmful actions, and refraining from intoxication. These vows are a foundation for laypersons but are stricter for monks. For monks, daily life involves adhering to stricter codes of conduct, like abstaining from luxurious items and engaging in meditation, chanting, and other spiritual practices. This philosophy teaches a way of life rooted in ethical conduct and inner peace. Today, the world is plagued with challenges like violence, political instability, and religious conflicts. Humanity faces grave moral crises, despite the advancements in science, technology, and communication. While these advancements have brought material prosperity, they have also intensified conflicts and divisions among people. Buddha emphasized the analysis of human emotions and stated that the mind is the ruler of all actions. Therefore, to regulate wrong tendencies, individuals must cultivate noble thoughts and walk on the path of virtue. Buddha offered this path in the form of the Buddhist Dhamma. Regarding mutual cooperation, Buddha said that there is no hatred greater than hatred itself, and this principle remains universally relevant. Thus, recognizing the factors that create hatred and eliminating them was a significant teaching of Buddha. He propagated the principles of moral and compassionate living through the Panchshila and the middle path, aimed at reducing human suffering. Today, as India and the world witness various religious tensions and conflicts, these challenges have become a matter of concern. In India, incidents of communal violence and caste-based exploitation have harmed numerous innocent lives. Hence, if India is to uphold secularism and religious freedom, it must adopt the principles of Buddhist equality, compassion, and non-violence.